Knowledge, Attitudes, and Practice of Biomimetic Dentistry among General Dentists and Specialists in Tripoli, Libya. - Asma Ghoul; Salama Shaban; Fatima Abusua (Khalij-Libya Journal of Dental and Medical Research, 2024)
Aim: The aim of this study was to evaluate knowledge, attitudes and Practice of biomimetic dentistry among general dentists and specialists in Tripoli, Libya. Methods: The questionnaire was designed to assess knowledge and opinion toward biomimetic dentistry among Libyan dentists in Tripoli, the questionnaire was consisted of 21 yes, no questions about biomimetic some biomimetic materials and techniques. Results: showed highest level of awareness has been founded among specialists (90.9%) and the lowest level was among general dentists, with 76.2% being aware of biomimetic materials. The percentage of awareness tends to increase with increase in years of experience. The study revealed that high percentages of dentists have a good knowledge about biomimetic materials and high percentage of them prefer using biomimetic materials. The study revealed there is an under-utilization of some biomimetic materials and techniques. Conclusion: The present study concludes that the lack of knowledge, unavailability and high cost constitute major obstacles to the use of biomimetic materials when compared to conventional methods. To fill these gaps, seamless education on biomimetic methodologies should be implemented into the curriculum of undergraduate dental studies. In addition, providing particular postgraduate courses about biomimetic dentistry would boost dentist ability and knowledge to use these recent techniques in their regular practice. الهدف: كان الهدف من هذه الدراسة هو تقييم المعرفة والمواقف والممارسة في طب الأسنان المحاكي الحيوي بين أطباء الأسنان العامين والمتخصصين في طرابلس، ليبيا. طرق الدراسة: تم تصميم الاستبيان لتقييم المعرفة والرأي حول طب الأسنان المحاكاة الحيوية بين أطباء الأسنان الليبيين في طرابلس، وكان الاستبيان يتكون من 21 سؤال نعم، لا حول المحاكاة الحيوية لبعض المواد والتقنيات الحيوية. النتائج: أظهرت أن أعلى مستوى للوعي كان بين المتخصصين (90.9%) وكان أدنى مستوى بين أطباء الأسنان العامين، حيث كان 76.2% على دراية بالمواد المحاكاة الحيوية. وتميل نسبة الوعي إلى الزيادة مع زيادة سنوات الخبرة. وكشفت الدراسة أن نسب عالية من أطباء الأسنان لديهم معرفة جيدة بالمواد المحاكاة الحيوية وأن نسبة عالية منهم يفضلون استخدام المواد المحاكاة الحيوية. وكشفت الدراسة عن وجود نقص في استخدام بعض المواد والتقنيات المحاكاة الحيوية.الخاتمة: خلصت الدراسة الحالية إلى أن نقص المعرفة وعدم التوافر والتكلفة العالية تشكل عقبات رئيسية أمام استخدام المواد المحاكاة الحيوية بالمقارنة مع الطرق التقليدية. لملء هذه الفجوات، ينبغي تنفيذ التعليم السلس حول منهجيات المحاكاة الحيوية في المناهج الدراسية لدراسات طب الأسنان الجامعية. بالإضافة إلى ذلك، فإن توفير دورات معينة للدراسات العليا حول طب الأسنان المحاكي الحيوي من شأنه أن يعزز قدرة طبيب الأسنان ومعرفته لاستخدام هذه التقنيات الحديثة في ممارساته المنتظمة